The Efficacy and Safety of Programmed Death-1 and Programmed Death Ligand 1 Inhibitors for the Treatment of Hepatocellular Carcinoma: A Systematic Review and Meta-Analysis - He, Shukang; Jiang, Weichao; Fan, Kai; Wang, Xiaobei (Frontiers in Oncology, 2021)
Background Hepatocellular carcinoma (HCC) is often diagnosed at an advanced stage where only systemic treatment can be offered. The emergence of immune checkpoint inhibitors (ICIs) provides hope for the treatment of HCC. In this study, we performed a meta-analysis to provide evidence for the efficacy and safety of ICIs in the treatment of HCC. Methods The following databases and websites were searched: Embase, PubMed, Cochrane Library and ClinicalTrials.gov. The primary endpoints were response rate (RR), disease control rate (DCR), progression-free survival (PFS) and overall survival (OS). Results Finally, twelve studies were included in this meta-analysis. When the corresponding outcome indicators and their 95% confidence intervals (CIs) were pooled directly, the overall RR, DCR, PFS and OS were 0.17 (0.15-0.19, I2 = 56.2%, P=0.009), 0.58 (0.55-0.61, I2 = 75.9%, P<0.001), 3.27 months (2.99-3.55, I2 = 73.0%, P=0.001), 11.73 months (10.79-12.67, I2 = 90.3%, P<0.001). Compared to the control group, treatment with ICIs significantly improved RR, PFS and OS, the OR and HRs were 3.11 (2.17-4.44, P<0.001), 0.852 (0.745-0.974, P=0.019) and 0.790 (0.685-0.911, P=0.001), respectively. However, no significant improvement in DCR was found in ICIs treatment in this meta-analysis. Conclusion HCC patients would benefit from ICIs treatment, however, more studies are needed in the future to provide more useful evidence for the treatment of HCC by programmed death-1 (PD-1) or programmed death ligand 1 (PD-L1) inhibitors.